Herbicidi in njihovi metaboliti v podtalni vodi - Bregar, Renata (Zdravstveno varstvo, 2003)
The development and use of pesticides has markedly stimulated agricultural productivity. Herbicide production accounts for 46 % of the total world production of pesticides. Triazines are the most widely used herbicides; they are mostly employed to control broad-leaved weeds and other vegetation. The majority of herbicides are applied directly to soil or are sprayed over fields. Because of large production, good solubility and high stability of herbicides, large amounts of these chemicals are released into the environmentwhere they enter surface and ground waters. Given the fact that underground water is often the major source of drinking water, monitoring herbicide levels is essential for achieving the water quality objectives The paper closes with the presentation of the results of herbicide levels measurements in the Ljubljansko polje and Ljubljansko barje ground water.
Keywords: herbicidi; pesticidi; pitna voda; podtalna voda